Analisis Ketersediaan Air dengan Metode F.J Mock Pada Daerah Persawahan Desa Poboya Palu Sulawesi Tengah - Setiyawan, Setiyawan; Andiese, Vera Wim; Anzar, Lisa Arnita (Jurusan Teknik Sipil Universitas Tadulako, 2017)
This study aims to analyze the availability of water and determine farming patterns planning for aggriculture. Research process begin from collecting data then conducting hidrology analysis to know if the water is sufficient to meet the water needs in fungsional field and planning the suitable farming patterns. To determine the ratio between the need and the availability of water, in this case for aggriculture sector, the analysis of hydrology and the calculation of water requirement on the paddy field were done. There are some methods which can be used: Penman’s Method modification, used to calculating the value of the evapotranspiration by considering the related meteorological factors such as the air temperature, humidity, wind speed, and sun radiation. By using F.J. Mock Method, the amount of water flow obtained from rain’s data, characteristics of hydrology flow area, and evapotranspiration can be calculated. According to the results of data analyzing with 46.642 km2 catchments area, show that availability of water in Poboya’s Irrigation field in the middle of January is 0,038 m3/sec meanwhile water requirement is 0,0078 m3/sec. From the result it can be concluded that water supply in Poboya’s Irrigation is enough to fullfill the needs of water on t he functional area, as well as by a farming pattern plans of Rice – Rice – Palawija